IMPLEMENTASI DEEP LEARNING DALAM MENUMBUHKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V SEKOLAH DASAR - Candra Nur Tri Kusuma; Anggraeni Siwi, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the deep learning approach in developing critical thinking skills of fifth-grade stud1ents at Mertan 03 Elementary School and identify obstacles faced in science learning. This study uses a qualitative descriptive method with observation, interview, and documentation techniques. The results show that the application of deep learning through the Problem Based Learning and Project Based Learning models can encourage students to actively analyze, discuss, and relate concepts to everyday life. However, there are obstacles in the form of differences in learning readiness, low student self-confidence, and limited learning time. Overall, this approach is effective in improving students' critical thinking skills.